PRODUKSI DAN PROFIL PROTEIN TANAMAN BAWANG MERAH AKIBAT PEMBERIAN BERBAGAI DOSIS PUPUK CAIR EKSTRAK KOTORAN AYAM - Eko Juwaningsih (Partner, 2008)
The aims of this research, are want to know about: 1) Respond extract liquid of chicken feces fermentation by production shallots, 2) Dosage extract liquid of chicken feces fermentation by production shallots, 3) The protein profile of shallots, 4) Forming or not specific protein by usage extract liquid of chicken feces fermentation.The result of the research analyzed by Rendomized Blok Design (RAK) have six (6) treatments (extract : 250 ml water) repeated many three are: A0 = 0 ml (without fertilizer), A1 = 0,5 ml extract liquid, A2 =  1,0 ml extract liquid, A3 = 1,5 mls extract liquid, A4 = 2,0 mls extract liquid, A5 = 2,5 mls extract liquid, A6 = An-organic fertilizer standard.  If responded of treatments advanced with honestly significant difference test (Uji Turkey) 5 %.  Measure highly is heavy wet umbi after grown.  The supporter data is analysis soil before grown, and after grown (in plants high production) and analysis plants towards absorption element nutrion. The protein profile used SDS-PAGE analysis to get the protein band and compare with protein marker. The samples for analyzis are shallots 1.5 months after planting.The result of the research indicated: 1) Usage extract liquid of chicken faeces fermentation influential production of shallots, 2) In A5 treatments giving high weight wet (2872,5 gr/plot atau 14,36 ton/ha), 3) The result of analyz are found total 16 bands of profile protein.  Treatments A3, A4 and A5 have 16 bands protein. The different of has or no the band and thick or thin of the protein’s band depend on kind, number and sequence of amino acid, 4) There is a specific (band 15) only in treatment A3, A4 and A5 with weight of molecule are 27,5 KDa possibility equated respond plant by usage extract liquid of chicken faeces fermentation.Key words: Extract liquid of chicken faeces fermentation, protein molecule of shallots